Pengaruh Risk Based Capital (Rbc) dan Hasil Investasi Terhadap Laba Perusahaan Asuransi Jiwa Yang Terdaftar di Ojk Periode 2017-2020 - Nestianty Yeca Pebriany; Isro’iyatul Mubarokah (Jurnal Ilmiah Wahana Pendidikan, 2022)
The activity that the researcher carried out was to examine how a life insurance company is affected by risk based capital (RBC) and also investment returns. It was found that these two factors had a significant impact on the company's business profits. This study uses a targeted sampling technique with the author making several criteria that have been adjusted. The author uses the classical assumption test to analyze the data. This test is used to test whether the multiple linear regression analysis with the SPSS program is appropriate. Tests show that companies with high levels of investment and risk-based capital (RBC) tend to perform better than companies with lower levels of RBC. Which means that there is a positive relationship between the independent variable and the dependent variable on the profit of life insurance companies at OJK in 2017-2018. Health insurance companies must maintain their level of health in order to provide their customers with the best possible service.